2015
DOI: 10.1016/j.envpol.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Medication type modifies inflammatory response to traffic exposure in a population with type 2 diabetes

Abstract: The association between residential traffic exposure and change in C-reactive protein over 2-years was evaluated using multivariate linear regression including interaction models for traffic and diabetes medication use/type (insulin vs. oral hypoglycemic agents (OHAs)). The study population was Puerto Rican adults (n = 356) residing in greater Boston with type 2 diabetes. Traffic was characterized as proximity to roads with >20,000 weekday traffic volumes, and multi-directional traffic density. Increases in CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…One explanation for this may be that individuals with diabetes usually have comorbidities and worse homeostatic mechanisms, and are more prone to environmental stressors [ 56 , 57 ]. Exposure to high traffic volume was shown to have a stronger impact among diabetic individuals on insulin, which could imply more complicated diabetes, expressing higher inflammatory profiles compared to those on oral hypoglycemic agents [ 58 ]. Participants using diabetic medication in this study were more likely to be overweight, to have cardiovascular diseases and higher C-reactive protein levels compared to the other participants.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this may be that individuals with diabetes usually have comorbidities and worse homeostatic mechanisms, and are more prone to environmental stressors [ 56 , 57 ]. Exposure to high traffic volume was shown to have a stronger impact among diabetic individuals on insulin, which could imply more complicated diabetes, expressing higher inflammatory profiles compared to those on oral hypoglycemic agents [ 58 ]. Participants using diabetic medication in this study were more likely to be overweight, to have cardiovascular diseases and higher C-reactive protein levels compared to the other participants.…”
Section: Discussionmentioning
confidence: 99%
“…This minority group is disadvantaged in terms of their socioeconomic status, and several lifestyle exposures (Lucas, Freeman, & Adams, 2016;Martell, Garrett, & Caraballo, 2016), that contributes to but does not adequately explain their many health disparities when compared to whites and other Hispanic groups (Beckett et al 1996). However, despite research showing evidence of disparities in diet and environment for Hispanics, the degree to which diet impacts island Puerto Ricans and environment affects continental Puerto Ricans is less well known Rioux, Tucker, Brugge, & Mwamburi, 2015). Research reveals differential exposures and outcomes between these two Puerto Rican groups as well, necessitating research that defines and attempts to understand these differences.…”
Section: Discussionmentioning
confidence: 99%
“…This may be in part due to the nature of ethnicity as a surrogate for latent factors, including SES, so that it's impact of exposure inequality is amplified (Collins, 2004). Research has not assessed the exposure of air pollution across Hispanic subgroups, but research has shown interactions between indirect measures of air pollution and disease for Puerto Ricans (Rioux, Tucker, Brugge, & Mwamburi, 2015). Given that 90% of Hispanics in the U.S live in urban areas (Quintero-Somaini, 2004), with higher proximity to roadways and combustion sources, this indicates higher exposures to traffic pollution as well as pollution from coal and oil combustion (Woghiren-Akinnifesi, 2013).…”
Section: Importance Of Environmental Exposures and Diet To Be Key Detmentioning
confidence: 99%